2009
DOI: 10.3748/wjg.15.4915
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein IgG and IgA: The association with milk-induced gastrointestinal symptoms in adults

Abstract: AIM:To study the association between serum levels of milk protein IgG and IgA antibodies and milk-related gastrointestinal symptoms in adults. METHODS:Milk protein IgG and IgA antibodies were determined in serum samples of 400 subjects from five outpatient clinics in Southern Finland. Subjects were randomly selected from a total of 1900 adults undergoing laboratory investigations in primary care. All 400 participants had completed a questionnaire on abdominal symptoms and dairy consumption while waiting for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
(38 reference statements)
2
14
2
1
Order By: Relevance
“…Food-specific IgG values may reflect exposure to a specific food [5]. In support of our results, decreased IgE levels were associated with elevated levels of IgG antibodies against milk in individuals who had developed a tolerance to cow’s milk after experiencing an allergy to the same product [17], and subjects drinking milk had higher levels of milk IgG in their sera than did non-milk drinkers in one study [18]. …”
Section: Discussionsupporting
confidence: 77%
“…Food-specific IgG values may reflect exposure to a specific food [5]. In support of our results, decreased IgE levels were associated with elevated levels of IgG antibodies against milk in individuals who had developed a tolerance to cow’s milk after experiencing an allergy to the same product [17], and subjects drinking milk had higher levels of milk IgG in their sera than did non-milk drinkers in one study [18]. …”
Section: Discussionsupporting
confidence: 77%
“…Hochwallner et al found that cow milk protein intolerance patients couldn't be distinguished from persons without cow milk protein intolerance on the basis of IgG subclass or IgA antibody levels to purified recombinant alpha S1-casein, alpha S2-casein, beta-casein, kappa-casein, alpha-lactalbumin, and beta-lactoglobulin [23]. Anthoni et al found that milk protein IgG but not milk IgA seemed to be associated with self-reported milk-induced gastrointestinal symptoms [22]. In our study, serum cow milk-specific IgG was elevated in 65 CMA patients, while the total IgG levels were increased in 20 patients.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study we employed electrochemiluminescence immunoassay method, which was more sensitive than the fluorescence-labeled antibody assays [21]. The diagnostic value of specific IgG antibodies against cow milk proteins (CMP) is controversial because the production of these antibodies is a normal physiologic response following exposure to CMP [22]. Hochwallner et al found that cow milk protein intolerance patients couldn't be distinguished from persons without cow milk protein intolerance on the basis of IgG subclass or IgA antibody levels to purified recombinant alpha S1-casein, alpha S2-casein, beta-casein, kappa-casein, alpha-lactalbumin, and beta-lactoglobulin [23].…”
Section: Discussionmentioning
confidence: 99%
“…The novelty of the present study is that IgG and IgA antibodies directed against milk and wheat were compared between subjects who all reported GI complaints, but who did or did not perceive themselves as intolerant to these foods. Dietary intake of the offending foods was also estimated, as dietary restrictions have been suggested to affect serum concentrations of the antibodies in some studies [ 22 24 ]. Milk/dairy consumption was lower and close to the level of statistical significance in those with than without perceived milk intolerance.…”
Section: Discussionmentioning
confidence: 99%